2001
DOI: 10.1152/ajpregu.2001.280.3.r908
|View full text |Cite
|
Sign up to set email alerts
|

CLA reduces antigen-induced histamine and PGE2release from sensitized guinea pig tracheae

Abstract: Conjugated linoleic acid (CLA) has been shown to enhance immune reactions such as lymphocyte blastogenesis and delayed-type hypersensitivity. We investigated the role of CLA in type I (immediate) hypersensitivity, using a guinea pig tracheal superfusion model for measuring antigen-induced airway smooth muscle contraction and inflammatory mediator release. Female Hartley guinea pigs were fed a diet supplemented with 0.25 g corn oil or linoleic acid/100 g of diet (control) or 0.25 g CLA/100 g of diet for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 25 publications
2
61
0
Order By: Relevance
“…A similar decrease in PGE 2 release from antigen-sensitized and -challenged guinea pig tracheas was shown in an earlier study (42). Dietary CLA has also been shown to decrease prostanoid levels in serum (37,38), bone (22), spleen (38), and cultured keratinocytes (24).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…A similar decrease in PGE 2 release from antigen-sensitized and -challenged guinea pig tracheas was shown in an earlier study (42). Dietary CLA has also been shown to decrease prostanoid levels in serum (37,38), bone (22), spleen (38), and cultured keratinocytes (24).…”
Section: Discussionsupporting
confidence: 83%
“…For example, it is unclear whether or not CLA decreases prostanoid and LT release through a histamine-related mechanism. We previously showed that tracheas from CLA-fed animals have decreased histamine release in response to antigen challenge (42). Because histamine induces release of the mediators measured (32), CLA could be acting through inhibition of histamine release rather than directly affecting prostanoid and LT synthesis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the present study, we did not attempt to address the issue how Ova exposure sensitized PCFs. However, it is well established that Ova exposure in guinea pigs produces substantial pulmonary inflammation (17,41) and increased the release of inflammatory mediators, such as histamine (40), bradykinin (24), and prostaglandins (18,40). Because all of these mediators are known to sensitize/stimulate PCFs (23), they are probably involved in Ova sensitization of PCFs.…”
Section: Dvh In Ova Guinea Pigs Involves At Least Partially the Supmentioning
confidence: 99%